Risk of infection of COVID-19 in pets from the perspective of their owners in Lima, Peru - Villegas, Gonzalo (2021)
The aim of this study was to evaluate the perception of pet owners about the risk of infection of their pets with COVID-19 in Lima, Peru. A virtual survey was prepared for clients of private veterinary services in Metropolitan Lima. The instrument collected demographic information, knowledge about the transmission of SARS-CoV-2, cases of human infection, handling of the pet during the pandemic and perception of the risk of infection of animals by COVID-19. The survey was answered by 408 pet owners. It was recognized that the main means of transmission of COVID-19 were infected people (93.6%). Respiratory problems were rarely observed in dogs (8.1%) and cats (2.2%). The majority perception of those surveyed was not to relate the respiratory problems of pets with COVID-19 (80.6%), but they showed concern for the affected health of their animal (79.7%). The practice of walking the pets was carried out more than once a day (38.1%), being more frequent not using protection for the animals (65.4%). The walk generally lasted between 10 to 20 minutes (45.4%), and around the block (46.2%) and in parks (36.0%). Hygiene and prevention measures taken after the walk were bathing and washing of paws (73.4%) in pets, and a combination of measures that included social distancing (80.4%), use of personal protective equipment (79.7%) and use of alcohol / disinfectant (60.8%), in the owners. The study shows a low perception of the risk of transmission of COVID-19 from humans to pets, a knowledge that must be reinforced by health authorities to safeguard the human-animal relationship based on responsible pet ownership practices.